Adsorption-based atmospheric water harvesting by passive radiative condensers for continuous decentralized water production. (5th May 2023) - Bai, S.; Tian, Y.; Zeng, Y.; Chao, L.C.; Pan, A.; Ho, T.C.; Chen, S.; Shang, J.; Tso, C.Y.
Graphical abstract: Highlights: Adsorption-based atmospheric water harvesting using passive radiative condensers was developed. Daily water production of ∼3.2 mL/g MIL-101-Cr (HF) or ∼678 mL/m 2 radiative cooler was achieved. Water harvesting performance under different climatic conditions was theoretically predicted. Abstract: Water scarcity is serious nowadays, due to the limited fresh water resources and growing world population. Transport of fresh water to remote areas is also challenging. It leads to the necessity of decentralized water production for mitigating water stressed conditions, which is especially beneficial to people having difficulty accessing fresh water in remote areas. Atmospheric water harvesting is a promising solution as atmospheric water is a huge renewable reservoir that can satisfy the needs of human beings. Adsorption-based atmospheric water harvesting (ABAWH) and passive radiative condensers are two possible methods already investigated, but it is of interest to apply passive radiative condensers to ABAWH systems, considering their merits and limitations. Herein, for the first time, we designed and demonstrated a novel dual single-bed ABAWH system with passive radiative condensers using MIL-101-Cr (HF) as the adsorbent and P(VdF-HFP) as the radiative condenser to capture and deliver water from air for decentralized fresh water production. Based on several outdoor experiments, the estimated water harvesting productivity is ∼3.2 mL/g MIL-101-Cr (HF)/day or ∼678 mL/m 2 P(VdF-HFP) radiative cooler/day with the ratio of adsorbent weight to cooler area at ∼214 g/m 2 during clear days in Hong Kong, with no degradation in performance of the prototype after several outdoor experiments over 40 days. Water harvesting performance under different climatic conditions, i.e., mid-latitude winter, mid-latitude summer and tropical, was also mathematically predicted. This study provides a new path toward quasi-continuous daytime and nighttime decentralized water production to mitigate the current water stress.